Increased Thromboxane A2 Levels in Pulmonary Artery Smooth Muscle Cells Isolated from Patients with Chronic Obstructive Pulmonary Disease - Abdullah A. Alqarni (Medicina, 2023)
Introduction: Pulmonary hypertension due to chronic obstructive pulmonary disease (COPD) is classified as Group 3 pulmonary hypertension, with no current proven targeted therapies. It has been shown that cigarette smoke, the main risk factor for COPD, can increase thromboxane A2 production in healthy human pulmonary artery smooth muscle cells and pulmonary artery endothelial cells, and that blocking the effect of increased thromboxane A2 using daltroban, a thromboxane A2 receptor antagonist, can inhibit cigarette smoke-induced pulmonary artery cell proliferation. However, it is largely unknown whether thromboxane A2 is increased in smokers with COPD. Therefore, the aim of this study was to assess the level of thromboxane A2 production in patients with COPD who smoke. Methods: Pulmonary artery smooth muscle cells from three smokers with COPD and three healthy donors were cultured in cell culture medium. The culture medium was collected and the thromboxane B2 (a stable metabolite of thromboxane A2) released in the culture medium was quantified using an ELISA kit. The data were normalised with the total protein concentration and then expressed in pg/mg protein. Demographic data were collected and baseline pulmonary function tests of patients with COPD were conducted. Results: The mean age of patients with COPD was 69 ± 7 years. All patients were smokers and had a mean smoking history of 39.66 ± 9.50 packs per year. The mean forced expiratory volume in one second, that is, FEV1%, and the ratio of forced vital capacity (FVC) to FEV1% of COPD patients were 63.33 ± 19.60% and 52.66 ± 14.64%, respectively. The results revealed that thromboxane A2 production was significantly increased in pulmonary artery smooth muscle cells from smokers with COPD (434.56 ± 82.88 pg/mg protein) compared with the thromboxane A2 levels in pulmonary artery smooth muscle cells from healthy donors (160 ± 59.3 pg/mg protein). Conclusions: This is the first report of increased thromboxane A2 production in pulmonary artery smooth muscle cells from smokers with COPD. This observation strongly suggests that thromboxane A2 can be used as a novel therapeutic target for the treatment of patients with COPD-associated pulmonary hypertension.